Evaluation of nZVI for the degradation of atrazine in heterogeneous Fenton-like systems at circumneutral pH. Issue 6 (December 2021) - Plaza, Jorge; Arencibia, Amaya; López-Muñoz, María José
Abstract: The requirement of acidification for the successful of the Fenton processes in water treatment has promoted the search for new strategies to work at pH close to neutrality. With this objective, in this work the use of nZVI has been evaluated for the oxidative elimination of 10 mg L −1 of atrazine at circumneutral pH with nZVI/UVA, nZVI/H2 O2, and nZVI/H2 O2 /UVA systems. While UVA irradiation of sole nZVI was ineffective for degrading the herbicide, the addition of H2 O2 boosted up the reaction, with the nZVI/H2 O2 /UVA system attaining the highest degradation rate. The inhibition of the reaction upon addition of tert-butanol as scavenger pointed out the significant role of hydroxyl radicals in the atrazine oxidation. The characterization of fresh and spent samples, carried out by XRD, SEM, TEM, and nitrogen adsorption-desorption experiments, confirmed the presence of ferric oxidized compounds responsible of the heterogeneous photo-Fenton-like reactions. On the basis of the degradation products determined by high performance liquid chromatography (HPLC), a scheme of atrazine degradation pathways in the ZVI/H2 O2 /UVA system was proposed in which the reaction is mainly initiated by alkylic oxidation rather than dechlorination. Finally, the effect on the atrazine oxidation rate of the water constituent species was analyzed in different water matrices (pure, supply, simulated and secondary effluent real water). Considered individually, Cl −, SO4 2−, HCO3 −, and DOC, showed a moderate inhibitory effect on atrazine degradation kinetics, but their combination could explain the significant decrease of efficiency detected in the real secondary effluent water compared to less complex matrices. Graphical Abstract: ga1 Highlights: At circumneutral pH H2 O2 addition is needed to activate atrazine oxidation by nZVI. Atrazine degradation by nZVI/H2 O2 /UVA is initiated mainly by alkylic chains oxidation. A heterogeneous Fenton-like mechanism is associated to nZVI/H2 O2 /UVA at neutral pH.